ความสัมพันธ์ระหว่างความหลากหลายทางพันธุกรรมของยีน X-prolyl aminopeptidase 1 ตำแหน่ง rs17095355 กับผู้ป่วยเด็กโรคท่อน้ำดีตีบตันในประเทศไทย - สรัลนุช แก้วเกียรติยศ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
Biliary atresia (BA) is a rare disease of infancy which is characterized by progressive fibrosclerosing obstruction of the extrahepatic biliary system, resulting in obstruction of bile flow. If untreated, it will result in cholestasis which can leads to progressive fibrosis and ultimately to cirrhosis. Despite many hypotheses have been suggested for the cause of BA, but its etiology still remains largely unknown, but one hypothesis reveals that BA is an immune-mediated disease. X-prolyl aminopeptidase 1 (XPNPEP1) is a gene involved in the metabolism of inflammatory mediators, which is shown to express in epithelial cells of the hepatobiliary system and has been suggested for its association with pathogenesis of BA. Moreover, SNPs may be different among races, and this SNP in Thai patients with biliary atresia have not yet been investigated.Therefore, the aim of this study was to examine whether there is an association between XPNPEP1 rs17095355 gene polymorphism and susceptibility to BA in Thai children. A total of 124 cases of BA and 114 controls were genotyped for XPNPEP1 rs17095355 polymorphism. The XPNPEP1 rs17095355 C/T genotype was determined by polymerase chain reaction (PCR) and direct sequencing. The result showed that the frequency of TT genotype (P = 0.0016) and T allele (P = 0.0025) were significantly associated with an increased risk of BA and there was no association between XPNPEP1 SNP and the occurrence of jaundice. In conclusion, the association between XPNPEP1 rs17095355 polymorphism and BA has been demonstrated, particularly with T allele confers increased susceptibility to the BA.